The 2014 European Elections in Romania – Media Frames and Their Implications in the Europeanization Process - Oana Ștefăniță; Dana Raluca Buturoiu (Romanian Journal of Communications and Public Relations, 2015)
This paper addresses the implications of the media in two major processes at the EU level – the process of Europeanization and the process of building a European identity. So, it analyses European subjects, by focusing on the visibility and the media framing of these subjects during the 2014 EU Parliament elections. Recent theoretical studies in the domain show that media could be one of the actors that might be responsible for influencing the Europeanization process – either in the sense of enabling the emergence and functioning of a European public sphere or in the sense of even preventing its birth. Thus, our empirical research aims at investigating the degree of Europeanization of the Romanian media discourse in order to reveal the current situation regarding the public sphere in Romania today. Since the content analysis indicates a low degree of visibility of the European issues and rather low levels of issue-specific frames that might sustain the development of a mature European identity, we can conclude that media still have to struggle to accomplish the transition from the national level to the European(ized) one.